Ocean Wave Utilization for Renewable Power Generation Using Wave Energy Converters (WECs): A Review - Faranisa Febiola; Kanthi Prihastika Wijaya; Richa Amalia Fatma; Riziq Maulana (Journal of Clean Technology, 2025)
The growing demand for electricity and the environmental impact of fossil fuel use have increased interest in renewable energy sources, including ocean wave energy. As a country with vast marine resources, Indonesia has significant potential to harness ocean waves as a clean and sustainable energy solution. This review explores various Wave Energy Converter technologies with a primary focus on the Oscillating Water Column system. The analysis covers ten recent studies that examine energy conversion efficiency, hydrodynamic performance, and field implementation. The findings indicate that the Oscillating Water Column system generally offers higher efficiency and greater operational stability than overtopping devices. Key factors influencing performance include wave height, wave period, chamber geometry, and turbine configuration. Case studies such as LIMPET in Scotland and OBREC in Italy provide evidence of real-world viability. Despite these advantages, challenges remain in terms of high construction costs, material durability in marine environments, and infrastructure limitations in coastal regions. This review highlights the importance of continued innovation, local adaptation, and policy support to enable the broader adoption of ocean wave energy, especially in island nations seeking to enhance energy resilience and reduce carbon emissions.